Island Peak - a Popular Destination for Mountaineering in the Himalayas. Methodological and Practical Aspects - Ioan BÎCA (Cluj University Press, 2023)
Island Peak is located in the Solu-Khumbu region of the Himalayas (Nepal), and is a destination for beginner climbers, for acclimatization (at the altitude of 5000-6000 m), and training (practicing techniques for moving on exposed rock and ice, traversing crevasses on metal ladders, climbing on fixed ropes, moving on ice ledges, abseiling). The popularity of the massif is because it was noticed and climbed for the first time by members of the British expedition in 1953, but also from other causes, such as: easy access on the Dinboche-Chukkung-PareshayaGyab route; the short and relatively easy standard ascent route, but with enough technical challenges (slope, exposed rock, ice plateau with crevasses, ice wall, and exposed rock, narrow ridge with ice ledges), the passage of which is good training for climbing peaks above 7000 m and testing climbing skills; the proximity of the southern face of the Lhotse Peak; scenic perspectives towards Lhotse summit (8516 m), to the Imja, Lhotse Shar, and Lhotse glaciers, to the Baruntse ridge (7000 m), and the iconic Ama Dablam Peak (6856 m).The basic work is the result of direct research carried out by the author on the Island Peak massif and highlights, on the one hand, its geomorphological features, and on the other hand, the methodological stages of organizing and carrying out an expedition on this peak, relevant from sport and medical point of view. Island Peak - o destinație populară pentru alpinism în Himalaya. Aspecte metodologice și practice. Vârful Island Peak este situate în regiunea Solu-Khumbu, din Munții Himalaya (Nepal) și reprezintă o destinație pentru alpiniștii începători, pentru aclimatizare (pe nivelul altimetric de 5000-6000 m) și antrenament (exersarea tehnicilor de deplasare pe rocă expusă și pe gheață, traversarea crevaselor pe scări metalice, cățărare pe corzi fixe, deplasare pe cornișe de gheață, coborâre în rapel). Popularitatea masivului este data de faptul că a fost remarcat și urcat pentru prima dată de către membrii expediției britanice din 1953, dar și din alte cauze, cum ar fi: accesul ușor pe ruta Dinboche-Chukkung-PareshayaGyab; traseul standard de ascensiune scurt și relativ ușor, dar cu suficiente provocări tehnice (pantă, rocă expusă, platou de gheață cu crevase, perete cu gheață și rocă expusă, creastă îngustă cu cornișe de gheață), a căror parcurgere reprezintă un bun antrenament pentru ascensiunea pe vârfurile de peste 7000 m și testarea abilităților de cățărare; proximitatea feței sudice a vârfului Lhotse; perspectivele scenice spre vf. Lhotse (8516 m), spre ghețarii Imja, Lhotse Shar și Lhotse, spre creasta Baruntse (7000 m) și spre vârful iconic Ama Dablam (6856 m). Lucrarea de bază este rezultatul cercetărilor directe efectuate de autor în asupra masivului Island Peak și evidențiază, pe de-o parte, trăsăturile geomorfologice ale acestuia, iar pe de altă parte etapele metodologice de organizare și desfășurare a unei expediții pe acest vârf, relevante din punct de vedere sportive și medical. Cuvinte-cheie: alpinism, trekking, mountaineering, Everest Base Camp Trek, summit day.  Received 2023 September 4; Revised 2023 September 28; Accepted 2023 October 2nd; Available online 2023 September 30; Available print 2023 November 30